Losing the race? Philosophy of race in U.K. philosophy departments. (15th January 2022) - Chauhan, Vipin; Crowley, Thomas; Fisher, Andrew; McCabe, Helen; Williams, Helen
Abstract: Should philosophy of race be taught as part of a philosophy degree? This paper argues that it should. After surveying 1, 166 modules on offer in 2019–2020, across forty‐seven philosophy departments in the United Kingdom, however, the authors identified only one module devoted to philosophy of race. The paper presents this as a challenge to philosophy departments. It investigates one possible reason for this that concerns staff research interests; indeed, reading 728 staff research webpages the authors identified only twenty‐three that listed philosophy of race as a research interest. Even though this might go some way to explaining the lack of modules, however, it can't be the whole picture. The paper suggests some areas relating to the philosophy curriculum in the United Kingdom that need some consideration.